Effective Guiding Proposals Applied to University Environmental Policy: A Response to the Challenges of Global Environmental Awareness - Rodríguez-Díaz, Yim James; Oñate, Zoraima Romero; Ochoa, Arley Denisse Vega (Journal of Posthumanism, 2025)
With the purpose of building emerging potential theory to strengthen guiding proposals for Higher Education Institutions (HEIs) associated with the successful implementation of environmental policy from the perspective of the Sustainable Development Goals (SDGs), the Continuous Comparative Method (CCM), based on the stages and processes of the Glaser and Strauss model, was applied. The study was supported by the theory of action of human behavior proposed by Argyris and Schön (1978), the concept of complexity (Morin, 2000), and the global challenges of humanity posed by Novo (1996), while also considering the feasibility of achieving the 2030 Sustainable Development Goals (UNDP–SDGs–Colombia, 2016). The research followed a qualitative approach, grounded in the interpretive paradigm, and employed grounded theory analysis (Strauss and Corbin, 2002). Data collection techniques included document analysis, semi-structured interviews, and participant observation. Key informants were three faculty members leading environmental management efforts and two administrative staff, who contributed to identifying: (i) The dimensions of environmental policies that either inhibit or promote the successful implementation of environmental management programs in higher education institutions. (ii) Guiding proposals to strengthen environmental policy in response to the challenges of global environmental awareness for sustainable development. The emerging proposals derived from the theory of action of social actors make it possible to understand the dynamics of the socio-natural environment and provide operational responses for the implementation, monitoring, and evaluation of the Environmental Management System (EMS), thereby contributing prospectively to the continuous improvement of environmental policy.